Obesity’s systemic impact: exploring molecular and physiological links to diabetes, cardiovascular disease, and heart failure - Banerjee, Dipanjan; Mani, Arya (Frontiers in Endocrinology, 2025)
Obesity prevalence continues to climb globally, driving healthcare costs ever higher. Over the past decade, significant strides have been made in understanding the causes of obesity, revealing that primary obesity is rooted in a complex interplay of genetic/developmental and epigenetic/environmental factors. Despite this progress, a critical gap remains in our understanding of the precise molecular pathways that translate adipose tissue expansion into the vast spectrum of associated comorbidities and heterogeneous patient outcomes. This review aims to synthesize recent mechanistic insights that bridge this gap. We summarize findings from extensive literature searches to highlight recent discoveries in the mechanisms underlying obesity and elucidate how these mechanisms contribute to various comorbidities. This review explores key pathways, including inflammation, insulin resistance, adipokine dysregulation, and complement system activation, that link obesity to diabetes, cardiovascular diseases, and metabolic syndrome. We provide a focused analysis of how these pathways drive two major obesity-related conditions: type 2 diabetes and cardiovascular disease, with particular emphasis on the pathophysiological mechanisms leading to heart failure. Additionally, we discuss the pathophysiological changes induced by obesity that directly contribute to the development of heart failure, including alterations in cardiac structure and function. Our findings highlight the intricate relationships between obesity and its comorbidities, emphasizing the need for a deeper understanding of these mechanisms to inform targeted interventions, druggable pathways, and improve management strategies for affected individuals.